2005
DOI: 10.1007/s10620-005-2557-1
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent Ethanol Ingestion Prevents Postischemic Leukocyte Adhesion and P-Selectin Expression by a Protein Kinase C?Dependent Mechanism

Abstract: The aim of this study was to determine whether protein kinase C (PKC) contributed to the effects of ethanol ingestion to prevent P-selectin expression, leukocyte rolling (LR), and stationary leukocyte adhesion (LA) induced by subjecting the small bowel to ischemia and reperfusion (I/R) 24 hr later. I/R increased P-selectin expression, LR, and LA, effects that were largely abolished by antecedent ethanol consumption. Exposing the bowel to a specific but nonisoform-selective PKC inhibitor (chelerythrine or bisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…However, studies conducted by our group that have focused on the mechanisms whereby antecedent ethanol induces the development of an anti-inflammatory phenotype such that postcapillary venules fail to support leukocyte adhesion on subsequent exposure to I/R suggest the role for NO/superoxide interactions, release of calcitonin gene-related peptide, and activation of specific protein kinase C isoforms (13,18,45,46,67,68). These observations, when coupled with the demonstration that leukocyte infiltration plays a critical role in the pathogenesis of cerebral I/R injury (69)(70)(71)(72), suggest that these signaling elements may contribute to the protective actions of antecedent ethanol ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies conducted by our group that have focused on the mechanisms whereby antecedent ethanol induces the development of an anti-inflammatory phenotype such that postcapillary venules fail to support leukocyte adhesion on subsequent exposure to I/R suggest the role for NO/superoxide interactions, release of calcitonin gene-related peptide, and activation of specific protein kinase C isoforms (13,18,45,46,67,68). These observations, when coupled with the demonstration that leukocyte infiltration plays a critical role in the pathogenesis of cerebral I/R injury (69)(70)(71)(72), suggest that these signaling elements may contribute to the protective actions of antecedent ethanol ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this work, several pharmacological agents are now known to induce a protective phenotype similar to that seen with IPC, such as PC with ethanol, adenosine receptor agonists, bradykinin, nitric oxide (NO) donors, and exogenous calcitonin gene-related peptide (4,9,26,41,43). Indeed, our own work (13,14,23,24,36,37,47) has established that these agents induced the development of a protective anti-inflammatory phenotype in postcapillary venules, such that these vessels fail to support adhesion molecule expression, leukocyte rolling and adhesion, and increased vascular permeability when the small bowel is subsequently exposed to prolonged ischemia-reperfusion (I/R).…”
mentioning
confidence: 99%
“…Results from several studies have shown that acute ethanol pretreatment/intoxication can offer protection to subsequent injury in multiple organs [10][11][12][13][14][15], including brain, heart, and intestine, et aletc. In spite of this, there is no direct convincing evidence for the protective effects of EtOH-PC to liver I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol preconditioning (EtOH-PC) refers to a phenomenon in which tissues are protected from the deleterious effects of ischemia/reperfusion (I/R) by prior ingestion of ethanol at low to moderate levels. There is evidence that moderate consumption of ethanol alone also exerts protective effects against injury due to cerebral, intestine, and myocardial ischemia [10][11][12][13][14]. It is suggested that low-dose ethanol attenuates the gut I/Rinduced hepatic microvascular dysfunction and sequential liver injury [15].…”
Section: Introductionmentioning
confidence: 99%